Pengaruh jaringan internet dan kesiapan sumber daya manusia keagenan kapal terhadap penerapan inaportnet di wilayah KUPP kelas II rangga ilung - Esa Hidayah; Jose Beno; Faris Nofandi; Anak Agung Istri Sri Wahyuni; Dian junita Arisusanty (IICET (Indonesian Institute for Counseling, Education and Therapy), 2024)
KUPP II Rangga Ilung Organizing Unit Office, in implementing ship activity document management services, changed services from manual to integrated and systemized services through the Inaportnet application on July 1, 2023. The implementation of Inaportnet at the KUPP II Rangga Ilung Office, there are obstacles, namely the internet network and the readiness of the ship agency's human resources. Therefore, it is hoped that these obstacles can be resolved. This research aims to determine the influence of the internet network and the readiness of ship agency human resources on the implementation of Inaportnet in the KUPP II Rangga Ilung Office area. The type of research used in this research is a combination method. This research was carried out at the KUPP II Rangga Ilung Office over a period of 7 months. The population used in this research is a purposive sampling technique which includes a non-probability method totaling 30 agency company samples. The data sources in this research use primary and secondary data using data collection techniques: observation, interviews, documentation, questionnaires, and literature review. With data analysis techniques, namely multiple linear regression tests. The results of this research are that the internet network variables and human resource readiness have a positive and significant effect together on the implementation of Inaportnet in the KUPP II Rangga Ilung Office area with a coefficient of determination influence value of 98%.